A 2 µm Gallium Antimonide Semiconductor Laser Based on Slanted, Wedge-Shaped Microlens Fiber Coupling - Zhaohong Liu; Jiayue Wang; Ning Li; Zhongwei Yang; Shaowen Li; Sensen Li; Wei Wang; Heshig Bayan; Weining Cheng; Yu Zhang; Zhuokun Wu; Hongyu Sun; et al. (Photonics, 2024)
Semiconductor lasers with a wavelength of 2 µm, composed of antimonide materials, find important applications in trace gas detection, laser medicine, and free-space optical communication, among others. In this paper, a more suitable microlens shape for 2 µm gallium antimonide semiconductor lasers is designed. Based on the fiber coupling efficiency model, the parameters of the designed slanting wedge-shaped microlens fiber are optimized to improve laser beam quality. The large tangent angle on both sides of the slanted, wedge-shaped microlens fiber is calculated using Snell’s law, and the fiber core diameter and small wedge angle are determined through space fiber coupling experiments. After packaging the fiber coupling module with the chip, the laser output beam exhibits good overall symmetry in the spot with a uniform intensity distribution. The maximum output power is approximately 210 mW, demonstrating good power stability.